Financial Literacy and Investment Motivation: The Role of Investment Interest in Investment Decisions (Case Study of Students from the Faculty of Economics, Yogyakarta) - Nur Anita Chandra Putry; Meri Grasia Elik (Equity: Jurnal Ekonomi, 2025)
This study aims to analyze the influence of financial literacy and investment motivation on the investment decisions of students in the Faculty of Economics in Yogyakarta, with investment interest as an intervening variable. Using a quantitative approach with an associative research design, primary data was collected through questionnaires distributed to students using the convenience sampling method. Data analysis was conducted using statistical techniques to examine the relationships between variables. The results indicate that financial literacy and investment motivation positively influence students' investment decisions. However, investment interest does not play a significant role as a mediator in this relationship. These findings highlight the importance of financial knowledge and investment motivation in enhancing student participation in the capital market. As an implication, this study recommends the development of more practical and experience-based financial education programs, such as investment simulations and financial management training, to better equip students in making informed investment decision